Sabun Cair Berbahan Dasar Olein Kelapa Sawit dengan Penambahan Ektrak Bandotan (Ageratum conyzoides L.) - Hendra Saputra; Yudi Dermawan; Sari Laras Wati (JURNAL CITRA WIDYA EDUKASI, 2019)
Palm oil contains oleic acid which acts as an antimicrobial in soap. The oil used is olein from palm oil which has been refined from the degumming, bleaching, deodorizing and filtering process to separate olein and stearin. Liquid soap is made from the reaction process between vegetable fats and potassium bases by the saponification process. The study purpose to determine the manufacture of olein-based liquid soap with the addition of Ageratum conyzoides extract and determine the optimal formulation for additional extracts in according with the Indonesian National Standard. Liquid soap is made as much as 4 variations of the addition of Ageratum conyzoides extract (0,5 ml, 7 ml and 9 ml). Testing the quality of liquid soap that has been made is adjusted to SNI 06-4085-1996 which includes observations of organoleptic, pH, free fatty acids, specific gravity of soap, moisture content, free alkali and high foam. The result of olein-based soap with the addition of Ageratum conyzoides extract can be made into liquid soap with an optimal formulation of 5 ml of Ageratum conyzoides extract. Based on the result of research and comparison with SNI, liquid soap with the addition of 5 ml of Ageratum conyzoides extract has the aroma of soy milk, pH according to skin pH 10.22, specific gravity of soap 1.0109 g/ml, free alkali 0.1485%, water content 78.4997%, high foam 88.1282 mm, and value of free fatty acids 0.1191%.